The role of varicocele treatment in the management of non-obstructive azoospermia (Clinics, 2013)
The literature on male reproductive medicine is continually expanding, especially regarding the diagnosis and treatment of infertility due to non-obstructive azoospermia. The advent of in vitro fertilization with intracytoplasmic sperm injection has dramatically improved the treatment of male infertility due to nonobstructive azoospermia. Assisted reproduction using testicular spermatozoa has become a treatment of hope for men previously thought to be incapable of fathering a child due to testicular failure. In addition, numerous studies on non-obstructive azoospermia have reported that varicocelectomy not only can induce spermatogenesis but can also increase the sperm retrieval rate; however, the value of varicocelectomy in patients with non-obstructive azoospermia still remains controversial. The purpose of this review is to present an overview of the current status of varicocele repair in men with non-obstructive azoospermia.